Corrosion Protection of Coated Steel Pipeline Structures using CP Technique - F. Al-Himdani, Fahim; Issa Mahdi, Wathik; Hassan Khuder, Abdul-Wahab (Journal of Engineering and Sustainable Development, 2005)
This work is directed toward the development of the corrosion resistance of the steel pipeline structures utilizing concrete coating using the cathodic protection technique to protect the structure of the coated steel pipeline structure. It deals with the matter of steel structures upon the survey periods, electrochemical dormant period because of the continuous cathodic prevention and the activation corrosion upon interruption period of this cathodic prevention and treatment this case of corrosion using the cathodic protection technique. The initial free corrosion potential (Ecorr) upon intermittently intervals and the corrosion rate measurement of the specimens using full polarization curve (Tafel Method) has been observed. The results clearly indicated that to achieve efficient design of a cathodic protection, the protected area should be divided into discrete electrochemical areas depending on the electrical resistance and steel potential to prevent the over-protection in the low electrical resistance areas when applying the designing criteria on the high electrical resistance areas. Furthermore, the results indicate that the absolute value of protection potential does not adequately describe the electrochemical changes undergone by the polarized coated steel pipe.